Pattern Design and Fitness of Business Jacket (Journal of Fiber Bioengineering and Informatics, 2012)
Modern design of business wear should not only meet the functional requirements, but also meet thefitness and aesthetics requirements. Research done in clothing companies show that unfitness hascurrently become an obstacle to the development of business wear enterprise. This paper points outthe problem and the design needs of an enterprise business jacket. From pattern to design method andease design as two aspects for further research, it is proposed that based on human characteristics of thebusiness jacket pattern to the design ideas, and through the samples wearing effects, evaluation shouldbe carried out to determine the exact ease and relevant parts that are free of business jacket. This studyaims to put forward business jacket pattern designs to provide a new method and for such wear designand distribution of ease to provide a reference basis, which acts as full of theoretical and practical values.